2022
DOI: 10.1108/ijoes-10-2021-0194
|View full text |Cite
|
Sign up to set email alerts
|

Ethical work climate and its influence on work-related ethical behaviour among the Malaysian public sector auditors

Abstract: Purpose The purpose of this paper are twofold. Firstly, it explores the extent to which ethical work climate (EWC) is prevalent among public sector auditors at the National Audit Department (NAD) of Malaysia. Secondly, it examines the relationship between EWC and the work-related ethical behaviour of public sector auditors in the NAD of Malaysia. Design/methodology/approach This study used a postal questionnaire survey, which was distributed to the public sector auditors in Malaysia. A total of 823 responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…The environment of the workplace also influences the performance and behaviour of organisational members (Obiora-Okafo & Imhanrenialena, 2022). It was also found that ethical work climate can influence the work-related ethical behaviour of Malaysian public sector auditors (Chew, Ismail, & Hassane, 2022). According to the Deep Learning Theory, informal learning spaces like the workplace will stimulate the deep learning process of individuals.…”
Section: Hypothesismentioning
confidence: 99%
“…The environment of the workplace also influences the performance and behaviour of organisational members (Obiora-Okafo & Imhanrenialena, 2022). It was also found that ethical work climate can influence the work-related ethical behaviour of Malaysian public sector auditors (Chew, Ismail, & Hassane, 2022). According to the Deep Learning Theory, informal learning spaces like the workplace will stimulate the deep learning process of individuals.…”
Section: Hypothesismentioning
confidence: 99%